Digital Teaching Materials Based Numeracy for Statistics in the Musi Banyuasin Context: Validity and Practicality Test - Bariyah, Leny; Susanti, Ely; Aisyah, Nyimas (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2025)
Numeracy skills can be supported by the use of digital teaching materials. One of them is digital teaching materials designed to support thinking skills to improve concentration and problem solving, with interesting features such as videos, images, and texts by only utilizing links and tools available on students' Android mobile phones. This study aims to produce valid and practical digital teaching materials and describe students' responses after using the game. The subjects of this study were 24 students of grade VII of SMP Negeri 4 Jirak Jaya. This research procedure uses a research design based on the Plomp development model. The Plomp development procedure consists of 4 phases, namely preliminary study, design phase, realization phase, and test, evaluation and revision phases. Data collection techniques used are questionnaires, observations, documentation, and interviews. Questionnaires are used to assess the validity and practicality of teaching materials. Observations are used to measure the effectiveness of learning. The data analysis technique used in this study is descriptive, both quantitative descriptive and qualitative descriptive. Based on the results of data analysis, it was obtained that the developed digital teaching materials fall into the valid category when viewed from the aspects of content, construction, language, and ICT. In addition, numeracy-based digital teaching materials also fall into the practical category when viewed from the aspects of ease of use, attractiveness, challenges, and their application in mathematics learning.